High-frequency resin substrate for antenna and preparation method thereof

By using a combination of ceramic composite powder and polytetrafluorovinyl base resin in the high-frequency resin substrate for antennas, the problem of dimensional instability of copper clad plate at extreme temperatures is solved, and the good dimensional stability of the high-frequency resin substrate is achieved.

CN119684732APending Publication Date: 2025-03-25JIANGSU ZHONGJIXIN COMM MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411953452.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The copper clad plate will shrink and swell at extreme temperatures, affecting the function of antennas or satellite components connected thereto, resulting in dimensional instability.

Method used

A high-frequency resin substrate for antennas is used, and its main components are polytetrafluorovinyl base resin and ceramic composite powder dispersed in the resin. The ceramic composite powder includes negative thermally expanded ceramic powder and positive thermally expanded ceramic powder. The mass ratio of the ceramic composite powder and polytetrafluorovinyl base resin is 1: (0.5~2).

Benefits of technology

When the ambient temperature of this high-frequency resin substrate changes, the contraction and expansion of the ceramic composite powder are offset by the expansion, and the overall volume changes are small, and it has good dimensional stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a high-frequency resin substrate for an antenna, the main components of the high-frequency resin substrate are polytetrafluoroethylene base material resin and ceramic composite powder dispersed in the base material resin, the ceramic composite powder comprises negative thermal expansion ceramic powder and positive thermal expansion ceramic powder, and the mass ratio of the base material resin to the ceramic composite powder is 1: (0.5-2). According to the high-frequency resin substrate for the antenna, ceramic composite powder is adopted as a reinforcing material, and when the environment temperature changes, negative thermal expansion ceramic powder and positive thermal expansion ceramic powder in the ceramic composite powder are shrunk and expanded; the high-frequency resin substrate is small in overall volume change and high in dimensional stability. The preparation process of the high-frequency resin substrate for the antenna is simple, and the high-frequency resin substrate for the antenna can be easily added into different shapes and sizes, so that large-scale production can be realized. The invention further discloses a preparation method of the high-frequency resin substrate for the antenna.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of copper clad laminates, and in particular to a high-frequency resin substrate for an antenna and a preparation method thereof. Background Art

[0002] The volume of copper clad laminates will shrink and expand due to temperature. Under extreme temperatures, the volume shrinkage of copper clad laminates may even affect the functions of components connected to the copper clad laminates; this requires copper clad laminates to have good dimensional stability, such as high-frequency resin substrates for antennas or satellites. Summary of the invention

[0003] One of the objects of the present invention is to provide a high-frequency resin substrate for an antenna, which substrate has good dimensional stability.

[0004] In order to achieve the above technical effects, the technical solution of the present invention is: a high-frequency resin substrate for an antenna, whose main components are a polytetrafluoroethylene base resin and a ceramic composite powder dispersed in the base resin, the ceramic composite powder includes a negative thermal expansion ceramic powder and a positive thermal expansion ceramic powder, and the mass ratio of the base resin to the ceramic composite powder is 1: (0.5~2).

[0005] The preferred technical solution is that the polytetrafluoroethylene base resin is made from polytetrafluoroethylene fraction resin powder, and the number average molecular weight of the polytetrafluoroethylene dispersed resin powder is 20 million to 30 million. Preferably, the number average molecular weight of the polytetrafluoroethylene dispersed resin powder is 20 million.

[0006] The preferred technical solution is that the negative thermal expansion ceramic powder is zirconium tungstate; and the positive thermal expansion ceramic powder is zirconium dioxide and silicon nitride.

[0007] The preferred technical solution is that the mass ratio of zirconium tungstate, zirconium dioxide and silicon nitride is 1: (1.8-2.2): (0.1-0.2).

[0008] A preferred technical solution is that the thickness of the high-frequency resin substrate for the antenna is 1-5 mm.

[0009] A second object of the present invention is to provide a method for preparing a high-frequency resin substrate for an antenna, comprising the following steps: S0: mixing negative thermal expansion ceramic powder and positive thermal expansion ceramic powder in proportion and then ball milling; first pressing the ball-milled material into a block, and then sealing and sintering at high temperature to obtain a sintered material; quenching and drying the sintered material and then grinding it to obtain a ceramic composite powder; S1: mixing polytetrafluoroethylene dispersed resin powder and ceramic composite powder in proportion at a temperature below -10°C to obtain a mixed powder, adding solvent oil to the mixed powder at room temperature to obtain a mixed material; S2: molding the mixed material into a blank; S3: placing the blank in an extruder to extrude a sheet, and calendering the sheet to form a film substrate of a predetermined size; S4: The film substrate is transferred into a high-temperature oven, the temperature is increased to remove the solvent oil and sintered to obtain a high-frequency resin substrate for a finished antenna.

[0010] The preferred technical solution is that in the S0 step, the average particle size of zirconium tungstate is 190-210nm, the average particle size of zirconium dioxide is 20-40nm, and the average particle size of silicon nitride is 450-550nm.

[0011] The preferred technical solution is that, based on the mass of the mixed powder as 100%, the mass of the solvent oil is 15% to 25% of the mass of the mixed powder; specifically 15%, 18%, 20%, 22%, 24%, 25%; further, the solvent oil is an isoparaffin solvent oil; the mixing process parameters of the polytetrafluoroethylene dispersed resin powder and the ceramic composite powder are: the mixing temperature is -80℃~-10℃, the stirrer speed is 1900~2200rpm, and the stirring time is 25~35min. The mixing of the polytetrafluoroethylene dispersed resin powder and the ceramic composite powder under low temperature conditions controls the fiberization of the polytetrafluoroethylene base resin, maintains the composite structure of the ceramic composite powder in the mixed powder, and accelerates the mixing of the polytetrafluoroethylene dispersed resin powder and the ceramic composite powder. Further, the mixing temperature is -80 to -60℃, preferably -80℃.

[0012] The preferred technical solution is that the temperature of the high temperature sintering in S0 is 1200-1220°C and the time is 20-24 hours.

[0013] The preferred technical solution is that the ball milling time is 10~12h, and the process of pressing into blocks is: using a pressing mold to statically press the ball-milled material, the static pressure is 100 Mpa, and the static pressure is until the ball-milled material does not drop debris; the particle size of the ceramic composite powder is 4~6um.

[0014] The advantages and beneficial effects of the present invention are: The high-frequency resin substrate for the antenna uses ceramic composite powder as a reinforcing material. When the ambient temperature changes, the negative thermal expansion ceramic powder and the positive thermal expansion ceramic powder in the ceramic composite powder shrink and expand; the overall volume change of the high-frequency resin substrate is small, and the dimensional stability is high.

[0015] The preparation process of the high-frequency resin substrate for the antenna is simple, and the high-frequency resin substrate for the antenna is easy to be added into different shapes and sizes, which is conducive to large-scale production. DETAILED DESCRIPTION

[0016] The specific implementation of the present invention is further described below in conjunction with the examples. The following examples are only used to more clearly illustrate the technical solutions of the present invention, and cannot be used to limit the protection scope of the present invention.

[0017] Solvent oil Solvent oil is used as an extrusion aid for polytetrafluoroethylene to increase the adhesion between polytetrafluoroethylene dispersed resin powders in the mixed powder and between polytetrafluoroethylene dispersed resin powders and ceramic composite powders, reduce the friction between polytetrafluoroethylene dispersed resin powders and extrusion equipment, and improve the mechanical properties of extrusion processing.

[0018] The optional range of solvent oil includes: isoparaffin solvent oil, paraffin oil, petroleum ether, kerosene, normal alkane solvent oil, preferably isoparaffin solvent oil.

[0019] raw material: PTFE resin powder: average particle size 450μm; Solvent oil: isoparaffin solvent oil, Isopar-M; Zirconium tungstate powder: average particle size 200nm; Zirconium dioxide powder: average particle size 30nm; Silicon nitride powder: average particle size 500 / 200nm.

[0020] 1. Examples and Comparative Examples Example 1

[0021] Embodiment 1 The method for preparing a high-frequency resin substrate for an antenna comprises the following steps: 1. Preparation of ceramic composite powder: 10 parts of zirconium tungstate powder, 20 parts of zirconium dioxide powder and 1 part of silicon nitride powder with an average particle size of 500nm are mixed in a blender to obtain a mixed material; the mixed material is placed in a planetary ball mill and ball-milled for 12 hours to obtain a ball-milled material, and the ball-milled material is statically pressed by a pressing mold with a static pressure of 100 MPa until the ball-milled material does not drop debris to obtain a block material; the block material is placed in a sealed platinum crucible and sintered at 1200°C for 24 hours to obtain a sintered material; the sintered material is quenched in ice water to obtain a quenched material; after drying and grinding the quenched material, particles with an average particle size of 5um are screened out with a sieve, which is a ceramic composite powder.

[0022] 2. Preparation of high-frequency resin substrate: S1: preparing two kinds of powders according to a mass ratio of 60:40 of polytetrafluoroethylene dispersion resin powder and ceramic composite powder, and preparing isoparaffin solvent oil according to a mass of isoparaffin solvent oil accounting for 18% of the sum of the mass of polytetrafluoroethylene dispersion resin powder and ceramic composite powder; S2: introducing polytetrafluoroethylene dispersed resin powder and ceramic composite powder into a low-temperature mixer, wherein the mixing chamber temperature of the low-temperature mixer is -80°C, the mixer speed is 2000 rpm, and the low-temperature stirring time is 30 minutes to obtain a mixed powder; adding solvent oil to the mixed powder at room temperature, mixing and stirring for 30 minutes to obtain a mixed material; S3: molding the mixed material into a blank under a pressure of 15 MPa; S4: placing the blank in an extruder to extrude a sheet, and placing the calendered sheet in a calender to form a film substrate with a width of 500 mm and a thickness of 1 mm; S5: The film substrate is sequentially transferred into a five-stage oven at 120 / 180 / 260 / 330 / 380°C, kept warm to remove the solvent oil and sintered for 20 minutes to obtain a finished high-frequency resin substrate.

[0023] Example 2 Based on Example 1, the difference is that the mass ratio of zirconium tungstate powder, zirconium dioxide powder and silicon nitride powder is 10:20:2.5.

[0024] Example 3 Based on Example 1, the difference is that the mass ratio of zirconium tungstate powder, zirconium dioxide powder and silicon nitride powder is 10:17:1.

[0025] Example 4 Based on Example 1, the difference is: Preparation of ceramic composite powder: Zirconium tungstate powder and zirconium dioxide powder are mixed in a blender at a mass ratio of 1:2, and then placed in a planetary ball mill for 12 hours to obtain mixed particles; the mixed particles and silicon nitride powder with an average particle size of 500nm are mixed at a mass ratio of 30:1 to obtain a mixed material; the mixed material is statically pressed using a pressing mold with a static pressure of 100 MPa until the mixed material does not drop debris to obtain a block material; the block material is placed in a sealed platinum crucible and sintered at 1200°C for 24 hours to obtain a sintered material; the sintered material is quenched in ice water to obtain a quenched material; after drying and grinding the quenched material, particles with an average particle size of 5um are screened out using a sieve, which is a ceramic composite powder.

[0026] Example 5 Based on Example 1, the difference is that the silicon nitride powder used is silicon nitride powder with an average particle size of 200 nm.

[0027] Comparative Example 1 Based on Example 1, the difference is S1: the two powders are configured according to a mass ratio of 70:30 between the polytetrafluoroethylene dispersion resin powder and the ceramic composite powder, and the isoparaffin solvent oil is configured such that the mass of the isoparaffin solvent oil accounts for 18% of the sum of the mass of the polytetrafluoroethylene dispersion resin powder and the ceramic composite powder.

[0028] 2. The high-frequency resin substrates of the embodiment and the comparative example were subjected to the following performance tests: 1. Use Keysight's network analyzer to test the dielectric constant (Dk) and dielectric loss (Df) of the sample copper-clad laminate at a frequency of 10 GHz. The number of test points is 10, and the average value is taken. 2. Detect the thermal expansion coefficient of high-frequency resin substrate at -55 ~ 288 ℃; 3. Evaluation of the folding resistance of high-frequency resin substrates.

[0029] 3. The test results of the high-frequency resin substrates of the embodiments and comparative examples are shown in the following table:

[0030] The "±N" of the dielectric constant in the above table represents the tolerance value of the dielectric constant of the substrate. The smaller N is, the smaller the tolerance of the dielectric constant is, and the higher the consistency of the product's dielectric performance is.

[0031] Compared with Example 1, the proportion of silicon nitride powder in the mixed material of Example 2 increases, and the proportion of zirconium dioxide powder in the mixed material of Example 3 decreases, indicating that the preferred mass ratio of zirconium tungstate powder, zirconium dioxide powder and silicon nitride powder in Example 1 is more conducive to preparing a ternary composite powder-filled substrate with a lower XYZ-axis thermal expansion coefficient.

[0032] In Example 4, zirconium tungstate powder and zirconium dioxide powder are first ball-milled and then mixed with silicon nitride powder, indicating that the simultaneous ball-milling of the three powders in Example 1 is conducive to obtaining a ternary composite powder-filled substrate with better particle size control, more uniform coating, and lower thermal expansion coefficient.

[0033] The silicon nitride powder used in Example 5 has an average particle size of 200 nm, indicating that the grading of the particle sizes of the three powders before ball milling will affect the XYZ-axis thermal expansion coefficient of the composite powder-filled substrate finally prepared; the grading of the particle sizes of zirconium tungstate powder, zirconium dioxide powder and silicon nitride powder in Example 1 is more conducive to preparing a ternary composite powder-filled substrate with a lower XYZ-axis thermal expansion coefficient.

[0034] In Comparative Example 1, the mass ratio of polytetrafluoroethylene dispersed resin powder to ceramic composite powder is 7:3, indicating that as the proportion of polytetrafluoroethylene dispersed resin powder increases, the influence of the ternary composite powder on the XYZ-axis thermal expansion coefficient of the filled substrate is significantly reduced, and the folding resistance of the substrate deteriorates.

[0035] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the technical principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A high-frequency resin substrate for an antenna, characterized in that: Its main components are polytetrafluoroethylene base resin and ceramic composite powder dispersed in the base resin, the ceramic composite powder includes negative thermal expansion ceramic powder and positive thermal expansion ceramic powder, and the mass ratio of the base resin to the ceramic composite powder is 1: (0.5-2).

2. The high-frequency resin substrate for antenna according to claim 1, characterized in that: The polytetrafluoroethylene base resin is made from polytetrafluoroethylene dispersed resin powder, and the number average molecular weight of the polytetrafluoroethylene dispersed resin powder is 20 million to 30 million.

3. The high-frequency resin substrate for antenna according to claim 1, characterized in that: The negative thermal expansion ceramic powder is zirconium tungstate; the positive thermal expansion ceramic powder is zirconium dioxide and silicon nitride.

4. The high-frequency resin substrate for antenna according to claim 3, characterized in that: The mass ratio of the zirconium tungstate, zirconium dioxide and silicon nitride is 1: (1.8-2.2): (0.1-0.2).

5. The high-frequency resin substrate for antenna according to claim 1, characterized in that: The thickness of the high-frequency resin substrate for the antenna is 1-5 mm.

6. A method for preparing a high-frequency resin substrate for an antenna, characterized in that: The following steps are involved: S0: mixing negative thermal expansion ceramic powder and positive thermal expansion ceramic powder in proportion and then ball milling; first pressing the ball-milled material into a block, and then sealing and sintering at high temperature to obtain a sintered material; quenching and drying the sintered material and then grinding it to obtain a ceramic composite powder; S1: mixing polytetrafluoroethylene dispersed resin powder and ceramic composite powder in proportion at a temperature below -10°C to obtain a mixed powder, adding solvent oil to the mixed powder at room temperature to obtain a mixed material; S2: molding the mixed material into a blank; S3: placing the blank in an extruder to extrude a sheet, and calendering the sheet to form a film substrate of a predetermined size; S4: The film substrate is transferred into a high-temperature oven, the temperature is increased to remove the solvent oil and sintered to obtain a high-frequency resin substrate for a finished antenna.

7. The method for preparing a high-frequency resin substrate for an antenna according to claim 6, characterized in that: In the S0 step, the average particle size of zirconium tungstate is 190-210 nm, the average particle size of zirconium dioxide is 20-40 nm, and the average particle size of silicon nitride is 450-550 nm.

8. The method for preparing a high-frequency resin substrate for an antenna according to claim 6, characterized in that: Taking the mass of the mixed powder as 100%, the mass of the solvent oil is 15% to 25% of the mass of the mixed powder; the solvent oil is an isoparaffin solvent oil; the mixing process parameters of the polytetrafluoroethylene dispersed resin powder and the ceramic composite powder are: the mixing temperature is -80°C to -10°C, the mixer speed is 1900 to 2200 rpm, and the stirring time is 25 to 35 min.

9. The method for preparing a high-frequency resin substrate for an antenna according to claim 6, characterized in that: The temperature of the high temperature sintering in S0 is 1200-1220° C., and the time is 20-24 hours.

10. The method for preparing a high-frequency resin substrate for an antenna according to claim 6, characterized in that: The ball milling time is 10-12 hours, and the process of pressing into blocks is: using a pressing mold to statically press the ball-milled material, the static pressure is 100 Mpa, and the static pressure is applied until the ball-milled material does not drop debris; the particle size of the ceramic composite powder is 4-6 um.